Age-Stereotype Internalization and Dissociation: Contradictory Processes or Two Sides of the Same Coin?. (December 2018) - Weiss, David; Kornadt, Anna E.
There is overwhelming evidence that age stereotypes have systematic effects on older adults' development. Regarding the direction of these effects, two seemingly opposing phenomena can be observed. On the one hand, it has been shown that older adults engage in self-stereotyping and assimilate their self-views and behavior to commonly held age stereotypes, a process described as stereotype internalization . On the other hand, there is considerable evidence for age-group dissociation, showing that when confronted with negative age stereotypes, older adults tend to distance and dissociate themselves from this negative stereotype. In addition to reviewing evidence for both processes and their respective adaptivity, we propose an integrated model of age-stereotype internalization and dissociation to explain when and why older adults internalize or dissociate from negative age stereotypes.